Application of the B-Determining Equations Method to One Problem of Free Turbulence - Kaptsov, O.V.; Schmidt, A.V. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
A three-dimensional model of the far turbulent wake behind a self-propelled body in a passively stratified medium is considered. The model is reduced to a system of ordinary differential equations by a similarity reduction and the B-determining equations method. The system of ordinary differential equations satisfying natural boundary conditions is solved numerically. The solutions obtained here are in close agreement with experimental data.